The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4040/jkan.2014.44.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Late Effects, Social Adjustment, and Quality of Life in Adolescent Survivors of Childhood Leukemia

Abstract: Purpose: This study was conducted to examine the late effects, social adjustment, and quality of life in adolescents who had been completely treated for childhood leukemia and their parents. Methods: Participants consisted of 41 pairs of adolescent survivors (13-18 years) and their parents. Parents checked for their child's physical late effects. The Korean Version of Post-Traumatic Symptoms for psychological late effects, social functioning questionnaire for social adjustment and the PedsQL 4.0 Generic Core S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…A alteração do nervo óptico em todas as variantes da leu19cemia, embora seja mais comum na LLA, na infância, é constituída por uma urgência oftalmológica, já que o seu comprometimento tem impacto na visão do paciente. (21) A infiltração do nervo óptico foi relatada em 5% a 13% dos pacientes com leucemia. (22) Camera et al (23) observaram que a infiltração do nervo óptico leucêmico ocorre em 1,4% dos casos pediátricos com LLA.…”
Section: Manifestações Oftalmológicas Da Leucemiaunclassified
See 1 more Smart Citation
“…A alteração do nervo óptico em todas as variantes da leu19cemia, embora seja mais comum na LLA, na infância, é constituída por uma urgência oftalmológica, já que o seu comprometimento tem impacto na visão do paciente. (21) A infiltração do nervo óptico foi relatada em 5% a 13% dos pacientes com leucemia. (22) Camera et al (23) observaram que a infiltração do nervo óptico leucêmico ocorre em 1,4% dos casos pediátricos com LLA.…”
Section: Manifestações Oftalmológicas Da Leucemiaunclassified
“…Assim, de início, o tumor pode ser visto surgindo diretamente da papila, associado a uma lenta e progressiva piora da acuidade visual, ou ser evidenciado mais tardiamente um edema de papila (Figuras 39, 40) (16) associado a uma rápida piora da acuidade visual. (21) Quando ocorre dano ao nervo óptico, diz-se que aconteceu infiltração no sistema nervoso central; tendo o paciente uma sobrevida de 50% aos 6 meses, enquanto que em um ano, o óbito é de até 90%. (23) Outra consideração relevante é a conduta a ser utilizada, já que, a porção intra-orbitária do nervo óptico está fora do escopo da quimioterapia devido à barreira hemato-ocular, assim, a radioterapia externa, tem que ser avaliada (25) .…”
Section: Manifestações Oftalmológicas Da Leucemiaunclassified
“…A number of studies have examined the quality of life and psychosocial issues of childhood cancer survivors across different ethnic groups (Chan et al, 2014; Phillips & Jones, 2014; Zebrack & Landier, 2011), but there is a lack of understanding about the experiences of understudied ethnic groups such as Koreans. Recently, there have been more quantitative (e.g., Chung, Lee, Ryu, Han, & Kim, 2012; Hong, Park, Kim, & Choi, 2014; Oh, Lee, Kim, & Park, 2013; Rhee et al, 2014) and qualitative studies (e.g., Nam & Choi, 2013; You, 2006) on the psychosocial adjustment of childhood cancer survivors. Consistent with other findings, two authors of this article found in their previous studies that social stigma, in the form of bullying, harassment, prejudicial insults, avoidance, isolation, and employment discrimination, was common for Korean childhood cancer survivors (Kim, Yi, & Kim, 2014).…”
mentioning
confidence: 99%